Global Transcriptomic Analysis and Function Identification of Malolactic Enzyme Pathway of Lactobacillus paracasei L9 in Response to Bile Stress - Ma, Xiayin; Wang, Guohong; Zhai, Zhengyuan; Zhou, Pengyu; Hao, Yanling (Frontiers in Microbiology, 2018)
Tolerance to bile stress is crucial for Lactobacillus paracasei to survive in the intestinal tract and exert beneficial actions. In this work, global transcriptomic analysis revealed that 104 genes were significantly changed (log2FoldChange > 1.5, P < 0.05) in detected transcripts of L. paracasei L9 when exposed to 0.13% Ox-bile. The different expressed genes involved in various biological processes, including carbon source utilization, amino acids and peptide metabolism processes, transmembrane transport, transcription factors, and membrane proteins. It is noteworthy that gene mleS encoding malolactic enzyme (MLE) was 2.60-fold up-regulated. Meanwhile, L-malic acid was proved to enhance bile tolerance, which could be attributed to the intracellular alkalinization caused by MLE pathway. In addition, membrane vesicles were observed under bile stress, suggesting a disturbance in membrane charge without L-malic acid. Then, genetic and physiological experiments revealed that MLE pathway enhanced the bile tolerance by maintaining a membrane balance in L. paracasei L9, which will provide new insight into the molecular basis of MLE pathway involved in bile stress response in Lactic acid bacteria.